2012
DOI: 10.2478/v10222-011-0050-4
|View full text |Cite
|
Sign up to set email alerts
|

Phytosterol and α-Lipoic Acid Conjugates: Synthesis, Free Radical Scavenging Capacity and RP-LC-MS-APCI Analysis

Abstract: Plant sterols (PS) are bioactive compounds effective in reducing plasma cholesterol. Fatty acid esters of PS have improved solubility and blending properties when utilized in various food products. Naturally occurring α-lipoic acid (LA) and its reduced form dihydrolipoic acid (DHLA) are known for their antioxidant activity. In addition, they have shown an array of health benefi cial properties against obesity, diabetes, cancer, cardiovascular and infl ammatory diseases etc. Different LA conjugates have been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Flavonoids have a variable number of hydroxyl phenolic groups and excellent ferric and other transition metal chelation properties, which confer a significant antioxidant capacity (Martínez et al, 2002) and play an important role in plant defense and signaling for reproduction, pathogenesis and symbiosis (Rijke et al, 2006), The sterols identified through chromatographic techniques, such as campesterol and stigmasterol, have demonstrated antioxidant properties in vitro and in vivo (Madawala et al, 2012). These sterols are also associated with pathogen defense, which could be related to the activity against bacteria and fungi observed in this study (Ramakrisha and Ravishankar, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids have a variable number of hydroxyl phenolic groups and excellent ferric and other transition metal chelation properties, which confer a significant antioxidant capacity (Martínez et al, 2002) and play an important role in plant defense and signaling for reproduction, pathogenesis and symbiosis (Rijke et al, 2006), The sterols identified through chromatographic techniques, such as campesterol and stigmasterol, have demonstrated antioxidant properties in vitro and in vivo (Madawala et al, 2012). These sterols are also associated with pathogen defense, which could be related to the activity against bacteria and fungi observed in this study (Ramakrisha and Ravishankar, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to phenolic acids, lipoic acid and dihydrogen lipoic acid also showed a good antioxidant capacity. To provide better physiological functions, plant sterol esters of lipoic acid and dihydrogen lipoic acid were also synthesized. , Madawala et al synthesized phytosterol lipoate and phytosterol dihydrolipoate using a chemical method in the presence of DMAP and 1-ethyl-3-(3-(dimethylamino)­propyl)­carbodiimide hydrochloride . By contrast, phytosterol dihydrolipoate displayed a better scavenging capacity of 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical.…”
Section: Chemical and Enzymatic Structural Modifications Of Plant Ste...mentioning
confidence: 99%
“…125,126 Madawala et al synthesized phytosterol lipoate and phytosterol dihydrolipoate using a chemical method in the presence of DMAP and 1-ethyl-3-(3-(dimethylamino)propyl)carbodiimide hydrochloride. 125 By contrast, phytosterol dihydrolipoate displayed a better scavenging capacity of 1,1-diphenyl-2picrylhydrazyl (DPPH) free radical. Wang et al developed an enzymatic route to synthesize phytosterol lipoate with a conversion of 71% using C. rugosa lipase as a catalyst under optimal conditions for 96 h. 126 The antioxidant ability of phytosterol has been greatly improved by conjugating with lipoic acid.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Phytosterols(PS) are triterpenes, an important component of plant cells, and are commonly found in seeds, vegetable oils and grains. Common in nature are β-sitosterol, campesterol, stigmasterol and ergosterol [1].It has the physiological functions of lowering blood lipid [2,3] , lowering cholesterol [4][5][6] , preventing cardiovascular disease [7],anti-cancer [8], anti-oxidation, scavenging free radicals [9,10], enhancing immunity [11], anti-inflammatory [12,13] and so on. Especially in reducing blood lipids, PS and cholesterol have similar molecular structure, which can competitively inhibit the absorption of cholesterol in the human intestinal tract, thereby reducing blood lipids [14].…”
Section: Introductionmentioning
confidence: 99%